2020
DOI: 10.1088/1748-9326/ab76da
|View full text |Cite
|
Sign up to set email alerts
|

Role of vegetated coastal ecosystems as nitrogen and phosphorous filters and sinks in the coasts of Saudi Arabia

Abstract: Vegetated coastal ecosystems along the Red Sea and Arabian Gulf coasts of Saudi Arabia thrive in an extremely arid and oligotrophic environment, with high seawater temperatures and salinity. Mangrove, seagrass and saltmarsh ecosystems have been shown to act as efficient sinks of sediment organic carbon, earning these vegetated ecosystems the moniker 'blue carbon' ecosystems. However, their role as nitrogen and phosphorus (N and P) sinks remains poorly understood. In this study, we examine the capacity of blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Interestingly, C:N ratios were similarly high at the three sites ( Table 1 ). The influence of mangroves and seagrass meadows could explain the high C:N ratios within the rather shallow and enclosed lagoon waters: values as high as 33 and 41 have been reported in A. marina mangrove sediments in the Red Sea ( Saderne et al, 2020 ), while values over 30 were observed for tropical C. serrulata leaves, which increased under high temperatures and low nutrient concentrations ( Viana et al, 2020 ). In the case of the Phytoplankton site outside the lagoon, C:N ratios higher than the nearby KAUST Harbor waters ( Silva et al, 2019 ) can be explained by mixing with lagoon water or to its more oligotrophic nature, evidenced in the comparatively lower concentrations of inorganic nitrogen ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, C:N ratios were similarly high at the three sites ( Table 1 ). The influence of mangroves and seagrass meadows could explain the high C:N ratios within the rather shallow and enclosed lagoon waters: values as high as 33 and 41 have been reported in A. marina mangrove sediments in the Red Sea ( Saderne et al, 2020 ), while values over 30 were observed for tropical C. serrulata leaves, which increased under high temperatures and low nutrient concentrations ( Viana et al, 2020 ). In the case of the Phytoplankton site outside the lagoon, C:N ratios higher than the nearby KAUST Harbor waters ( Silva et al, 2019 ) can be explained by mixing with lagoon water or to its more oligotrophic nature, evidenced in the comparatively lower concentrations of inorganic nitrogen ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, ( Böer 1996 ), ( Barth 2006 ), ( Basyoni and Mousa 2009 ), and ( Al-Taisan 2016 ) studied the chemical characteristics of salt marsh plants and soil along the Saudi Coast. Additionally, the last century's increment of nitrogen and phosphorous sequestration and the increased of elemental burial in salt marshes and other ecosystems along the Saudi coast was highlighted by ( Saderne et al, 2020 ) and ( Rabaoui et al, 2020 ) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabian Gulf is a shallow sea located in a subtropical arid zone ( Jones et al, 2012 ). Vegetated coastal ecosystems along the Arabian Gulf thrive in a hyper-arid and oligotrophic environment, with high levels of seawater temperatures and salinity ( Saderne et al, 2020 ). The majority of Arabian Gulf countries lacked freshwater input ( Brown et al, 2018a , Brown et al, 2018b ) and were affected by the largest oil spill in history from the 1991 Gulf war ( Boer 1996 ), with 11 million barrels of crude oil that were discharged in the sea ( Michel 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Arabian Gulf is a shallow sea characterized by high levels of seawater temperature and salinity [ 7 ]. High temperatures and shallow waters are found particularly on the west coast in front of the Gulf’s states.…”
Section: Introductionmentioning
confidence: 99%